2024
DOI: 10.3390/ani14030517
|View full text |Cite
|
Sign up to set email alerts
|

Population Analysis Identifies 15 Multi-Variant Dominant White Haplotypes in Horses

Aiden McFadden,
Micaela Vierra,
Holly Robilliard
et al.

Abstract: The influence of a horse’s appearance on health, sentimental and monetary value has driven the desire to understand the etiology of coat color. White markings on the coat define inclusion for multiple horse breeds, but they may disqualify a horse from registration in other breeds. In domesticated horses (Equus caballus), 35 KIT alleles are associated with or cause depigmentation and white spotting. It is a common misconception among the general public that a horse can possess only two KIT variants. To correct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The proto-oncogene c-kit is located on chromosome 3 in horses and affects the survival, migration, and differentiation of melanocytes. It is a major candidate gene for the formation of white coat color [ 78 , 79 , 80 ]. Previous studies have shown that four white coat color traits, Dominant White, Tobiano, Sabino, and Roan, are associated with the KIT gene, as depicted in Table 3 .…”
Section: Candidate Genes Associated With Coat Color Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The proto-oncogene c-kit is located on chromosome 3 in horses and affects the survival, migration, and differentiation of melanocytes. It is a major candidate gene for the formation of white coat color [ 78 , 79 , 80 ]. Previous studies have shown that four white coat color traits, Dominant White, Tobiano, Sabino, and Roan, are associated with the KIT gene, as depicted in Table 3 .…”
Section: Candidate Genes Associated With Coat Color Phenotypesmentioning
confidence: 99%
“…This finding may help explain the appearance of the cryptic Tobiano phenotype [ 36 , 86 ]. Similarly, Brooks et al [ 80 ] identified a single nucleotide polymorphism resulting from a T and A base substitution in intron 16 and a subsequent deletion in exon 17, leading to the formation of Sabino 1 (SB1). However, this specific polymorphism cannot fully account for the various Sabino types observed.…”
Section: Candidate Genes Associated With Coat Color Phenotypesmentioning
confidence: 99%